Les risques sanitaires des produits dérivés de la chloration des eaux de bassins de natation - Sylviane Carbonnelle (Éditions en environnement VertigO, 2003)
Swimming pools are attended by a lot of people worldwide, to swim or to relax. However, the chlorinated atmosphere of swimming pools may be responsible for health problems. Indeed, the majority of swimming pools are disinfected by chlorine based products –leading to the formation of potentially toxic derivatives- and studies have recently drawn attention to health risks linked to the attendance of swimming pools. It has been suggested among other things that the increasing and earlier exposure of children to swimming pools chlorination by-products could, in association with other factors, be implicated in the increasing incidence of asthma and allergies. For the moment, prevention measures should be taken to decrease the risk linked to the exposure to these derivatives (reduction in their formation or in their accumulation at least).